Capacitor voltage balancing control with reducing the average switching frequency in MMC. Issue 16 (18th January 2019) - Wang, Shunliang; Liu, Tianqi; Huang, XingChuan; Yu, Yuexiao
Abstract : Modular multilevel converter (MMC) has a very good application prospect in the flexible high‐voltage direct current (HVDC) transmission, but higher self‐loss will affect the efficiency and restrict the development. Here, the MMC in voltage source converter‐based HVDC as the research object, the control and modulation algorithms are designed on the basis of analysing its working principle. The capacitor voltage imbalance problem is existed in the converter because that the capacitor of each module is independent. The factors of switching actions in balancing control technology based on the sorting method of sub‐module capacitor voltages are analysed in detail. Then, an optimised balancing control algorithm by setting two balancing control thresholds is proposed to reduce the average switching frequency. Finally, a two ends HVDC transmission system was built in MATLAB/SIMULINK to verify the optimisation. The simulation research results show that the optimised balancing control can ensure sub‐module capacitor voltage is in balanced and does not increase the AC output voltage harmonic content, and obviously reduce the average switching frequency of switching devices, and with the increase of number of level, the more obvious optimisation effect.